Mental Health Status of Healthcare Workers during the COVID-19 Outbreak: An International Study - Nicolaou, Christiana; Menikou, Joanna; Lamnisos, Demetris; Lubenko, Jelena; Presti, Giovambattista; Squatrito, Valeria; Constantinou, Marios; Papacostas, Savvas S.; Aydln, Gokcen; Chong, Yuen Yu; Chien, Wai Tong; Cheng, Ho Yu; et al. (My University, 2021)
Background: The COVID-19 pandemic is a massive health crisis that has exerted enormous physical and psychological pressure. Mental healthcare for healthcare workers (HCWs) should receive serious consideration. This study served to determine the mental-health outcomes of 1,556 HCWs from 45 countries who participated in the COVID-19 IMPACT project, and to examine the predictors of the outcomes during the first pandemic wave. Methods: Outcomes assessed were self-reported perceived stress, depression symptom, and sleep changes. The predictors examined included sociodemographic factors and perceived social support. Results: The results demonstrated that half of the HCWs had moderate levels of perceived stress and symptoms of depression. Half of the HCWs (n = 800, 51.4%) had similar sleeping patterns since the pandemic started, and one in four slept more or slept less. HCWs reported less perceived stress and depression symptoms and higher levels of perceived social support than the general population who participated in the same project. Predictors associated with higher perceived stress and symptoms of depression among HCWs included female sex, not having children, living with parents, lower educational level, and lower social support. Discussion: The need for establishing ways to mitigate mental-health risks and adjusting psychological interventions and support for HCWs seems to be significant as the pandemic continues.
Keywords: Healthcare workers; COVID-19; Pandemic; Mental health; Psychological problems